Causes and Risk Factors of Urinary Incontinence: Avicenna’s Point of View vs. Contemporary Findings - Nojavan, Fatemeh; Sharifi, Hossein; Ghanbari, Zinat; Kamalinejad, Mohammad; Mokaberinejad, Roshanak; Emami, Maryam (Urology Journal, 2015)
Abstract Purpose: To extract the causes and risk factors of urinary incontinence from an old medical text by Avicenna entitled "Canon of Medicine" and comparing it with contemporary studies. Materials and Methods: In this study, etiology and risk factors of urinary incontinence were extracted from Avicenna’s "Canon of Medicine". Commentaries written on this book and other old reliable medical texts about bladder and its diseases were also studied. Then the achieved information was compared with contemporary findings of published articles. Results: Urinary incontinence results from bladder dysfunction in reservoir phase. Bladder’s involuntary muscles and voluntary external sphincter are two main components which are involved in this process. Urinary incontinence can exist without obvious structural and neuronal etiologies. According to Avicenna, distemperment of muscular tissue of bladder and external sphincter is the cause for urinary incontinence in such cases. Distemperment is the result of bothering qualities in tissue, i.e.: "wet" and "cold". They are the two bothering qualities which are caused by extracorporeal and intracorporeal factors. Interestingly, the positive associations of some of these factors with urinary incontinence have been shown in recent researches. Conclusion: "Cold" and "wet" distemperment of bladder and external sphincter can be independent etiologies of urinary incontinence which should be investigated.